2018
DOI: 10.1590/1981-22562018021.170114
|View full text |Cite
|
Sign up to set email alerts
|

Influence of symptoms of depression on the quality of life of men diagnosed with prostate cancer

Abstract: Objective: to evaluate the prevalence of symptoms of depression among men diagnosed with prostate cancer and their association with quality of life and treatment-related factors. Methods: a cross-sectional study of 85 men with a mean age of 66±8 years who were diagnosed with prostate cancer was performed. The survey was based on a questionnaire with previously validated instruments which investigated social, demographic and economic characteristics, the history of the disease, quality of life (European Organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
2
0
3
Order By: Relevance
“…52,53 Seeman et al, 2018 showed that depressive symptoms had a significant negative effect on the QOL of men with CaP. 54 We were unable to account for the correlation between the CES-D and STAI-S with HRT symptoms despite participants not being exposed to ADT. It is possible that this may in part be attributed to late onset hypogonadism (LOH).…”
Section: Discussionmentioning
confidence: 91%
“…52,53 Seeman et al, 2018 showed that depressive symptoms had a significant negative effect on the QOL of men with CaP. 54 We were unable to account for the correlation between the CES-D and STAI-S with HRT symptoms despite participants not being exposed to ADT. It is possible that this may in part be attributed to late onset hypogonadism (LOH).…”
Section: Discussionmentioning
confidence: 91%
“…Although survival rates have risen and advances in diagnosis and treatment have been made, cancer is still received as a death sentence and brings with it psychological consequences such as fear, sadness and depression [5]. In addition, it is known that there are complications from prostate cancer treatment that can have an impact on urinary and sexual function, such as urinary incontinence and erectile dysfunction that affect marital life and generate losses in the quality of life of patients, including the psychological aspect [6].…”
Section: Resultsmentioning
confidence: 99%
“…A depressão é uma das principais repercussões psicológicas que interferem na qualidade de vida dos homens acometidos pelo CP, pois, além da repercussão clínica, o paciente convive diariamente com a dor física e risco de morte relativos à ocorrência de possíveis metástases e recorrência da doença. Além disso, o medo da impotência sexual, angústia da perda de controle urinário, incapacidade de ter ereções satisfatórias e insegurança de ser abandonado pela parceira/o sexual; são alguns sentimentos expressos pelos pacientes com CP, afetando a qualidade de vida no que diz respeito à saúde física e emocional desses homens (Seemann et al, 2018).…”
Section: Sinais E Sintomasunclassified